All physical activity may not be associated with a lower likelihood of adolescent smoking uptake. (December 2015) - Audrain-McGovern, Janet; Rodriguez, Daniel
Abstract: Objective: Research has documented that physical activity is associated with a lower risk of adolescent smoking uptake, yet it is unclear whether this relationship exists for all types of physical activity. We sought to determine whether certain types of physical activity are associated with a decreased or an increased risk of adolescent smoking uptake. Methods: In this longitudinal cohort study, adolescents (n = 1356) were surveyed every six months for four years (age 14–18 years old). Smoking and physical activity were measured at each of the eight time-points. Physical activity that was negatively associated with smoking across the eight waves was considered positive physical activities (i.e., PPA; linked to not smoking such as racquet sports, running, and swimming laps). Physical activity that was positively associated with smoking across the eight waves were considered negative physical activities (i.e., NPA; linked to smoking such as skating, walking, bicycling, sport fighting, and competitive wrestling). Results: Associative Processes Latent Growth Curve Modeling revealed that each 30-minute increase in NPA per week at baseline was associated with a 4-fold increased odds of smoking progression (OR = 4.10, 95% CI = 2.14, 7.83). By contrast, each 30-minute increase in PPA at baseline was associated with a 51% decrease in the odds of smoking progression (OR = .49, 95% CI = .25, .93). Conclusions: The type of physical activity that an adolescent engages appears to be important for the uptake of cigarette smoking among adolescents. These associative relationships warrant consideration in interventions to increase overall physical activity and those promoting physical activity to prevent smoking uptake. Highlights: Some types of physical activity are associated with lower odds of smoking uptake Other types of physical activity are associated with greater odds of smoking uptake These associations may be important to consider in smoking prevention interventions